(3eTcdI GdMOhO GdLfhHjI GdTQbjI deUQ (B: s (3OQGSI bGfhfjI OhdjI (B/ s - (3Tje MGeO YHOGdMejO GdLQa s; (3UdGM GdOjf YGeQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3JJHY GgejI GdOQGSI ef WHjYI GdYdGbGJ GdeUQjI GdShOGfjI hNUhUjJgG (B: (3hebJVj Pdc eMGhdI GdJhUd dMd deG bO jYJQj Jdc GdYdGbGJ ef eSGFd NdGajI (B: (3hGdJj JYO hVY GdMOhO GdLfhHjI GdTQbjI deUQ GMOgG(B. (3hgh eGQcR Ydjg GdHMK ef OQGSI haGb (B19 (3jfGjQ (B1899 (3egO GdMOhO GdLfhHjI deUQ hGdTeGdjI ddShOGfs
(3jTJed Ydi edGMbs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdj, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B221-231s
Keywords: (3GdbGfhf GdOhdjs; (3GdShOGf s; (3MOhO s; (3eUQ s; (3MdGjH hTdGJjf s; (3Mb JbQjQ GdeUjQ s; (3GOYGAGJ GdSGOI GdShOGfjI s; (3hXGFa GdMOhO GdOhdjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs